The Lyman‐α Sky Background as Observed by New Horizons. Issue 16 (23rd August 2018) - Gladstone, G. Randall; Pryor, W. R.; Stern, S. Alan; Ennico, Kimberly; Olkin, Catherine B.; Spencer, John R.; Weaver, Harold A.; Young, Leslie A.; Bagenal, Fran; Cheng, Andrew F.; Cunningham, Nathaniel J.; Elliott, Heather A.; et al.
Abstract: Recent observations of interplanetary medium atomic hydrogen Lyman‐α emission in the outer solar system, made with the Alice ultraviolet spectrograph on New Horizons, are presented. The observations include regularly spaced great circle scans of the sky and pointed observations near the downstream and upstream flow directions of interstellar H atoms. The New Horizons Alice data agree very well with the much earlier Voyager UVS results, after these are reduced by a factor of 2.4 in brightness, in accordance with recent reanalyses. In particular, the falloff of interplanetary medium Lyman‐α brightness in the upstream‐looking direction as a function of spacecraft distance from the Sun is well matched by an expected 1/ r dependence, but with an added constant brightness of ~40 Rayleighs. This additional brightness is a possible signature of the hydrogen wall at the heliopause or of a more distant background. Ongoing observations are planned at a cadence of roughly twice per year. Plain Language Summary: Long‐term observations made with the Alice instrument on the New Horizons spacecraft confirm measurements made 30 years earlier with the Voyager spacecraft. Both sets of data are best explained if the observed ultraviolet light is not only a result of the scattering of sunlight by hydrogen atoms within the solar system but includes a substantial contribution from a distant source. This distant source could be the signature of a "wall" of hydrogen, formed near where the interstellar wind encounters the solar wind, or could be more distant. Similar future observations from New Horizons are planned about twice each year. Key Points: New Horizons Alice observations of interplanetary medium Lyman alpha are presented The observed brightness falloff with distance from the Sun matches well with Voyager results and indicates a substantial external background contribution